2012
DOI: 10.1093/treephys/tpr135
|View full text |Cite
|
Sign up to set email alerts
|

Novel Prunus rootstock somaclonal variants with divergent ability to tolerate waterlogging

Abstract: Plants require access to free water for nutrient uptake, but excess water surrounding the roots can be injurious or even lethal because it blocks the transfer of free oxygen between the soil and the atmosphere. Genetic improvement efforts in this study were focused on the increased tolerance in roots to waterlogging. Among a pool of clones generated in vitro from leaf explants of rootstock Mr.S.2/5 of Prunus cerasifera L., the S.4 clone was flood tolerant whereas the S.1 clone was sensitive. The S.4 clone form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 48 publications
7
30
1
Order By: Relevance
“…Prunus cerasifera L. clones (Pistelli et al, 2012) tolerant and sensitive to hypoxia had high total antioxidant capacity in the leaves when the roots were under hypoxia. Lacerda (2013) demonstrated that the damage caused by hypoxia in the roots of these same clones was faster and more intense than the damage under high Mn concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Prunus cerasifera L. clones (Pistelli et al, 2012) tolerant and sensitive to hypoxia had high total antioxidant capacity in the leaves when the roots were under hypoxia. Lacerda (2013) demonstrated that the damage caused by hypoxia in the roots of these same clones was faster and more intense than the damage under high Mn concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of tropical and subtropical fruit trees show anatomical or morphological adaptations to flooding stress, such as the development of hypertrophied stem lenticels, adventitious rooting or the formation of porous aerenchyma tissue (Schaffer et al, 2006). Aerenchyma formation in response to low oxygen availability has been reported as an anatomical adaptation to facilitate gas diffusion (like O 2 ) between hypoxic/ anoxic roots and the aerial environment, including Prunus rootstocks (Garthwaite et al, 2008;Pistelli et al, 2012). Under hypoxia, aerenchyma formation involves cell death caused by an enhanced rate of ethylene synthesis (Jackson, 1985;He et al, 1994;Gunawardena et al, 2001).…”
Section: Waterlogging Causes Anatomical Physiological and Molecular mentioning
confidence: 99%
“…Epinasty, a common response in flooded plants, results from accumulation of the ethylene precursor ACC in roots; basically, ACC is transported through the transpiration stream to the aerial part of the plant, where the presence of oxygen allows it to be converted into ethylene, triggering petiole epinasty (Jackson, 2008;Vidoz et al, 2010). In Prunus cerasifera Ehrh., while the wild-type was sensible to flooding, showing epinasty and leaf senescence, the L clone showed an increase in ethylene synthesis (mainly in leaves) and ACC oxidase (ACO) gene expression (Pistelli et al, 2012). In Citrus, water-stress induced leaf abscission was associated with ACC expression accompanied by a concomitant increase in ethylene (Gómez-Cadenas et al, 1996).…”
Section: Ethylene Could Play An Important Role Under Waterlogging Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, plants need free access to water for nutrient absorption, excess water around roots can be harmful or even lethal, since it reduces drastically the transfer of free oxygen between the soil solution and the atmosphere (PISTELLI et al, 2012). This condition, decreasing the oxygen levels in the environment around the roots, inducing root asphyxia and greatly damaging critical periods of the crop, as it is the case of the blossoming period and beginning of sprouting (MARTINAZZO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%